An Improved liquid Culture System for Efficient Shoot Multiplication in Aerva lanata (L.) Juss. Ex Schult. (Plant Tissue Culture and Biotechnology, 2021)
An improved in vitro mass propagation protocol was developed for Aerva lanata using MS liquid medium. The influence of MS medium (solid and liquid) with cytokinin (TDZ and BAP, respectively) were studied for shoot proliferation and growth. The liquid medium perfomed better than solid medium in shoot multiplication. The maximum shoot multiplication rate was (29.37 ± 0.64 shoots per explant), obtained in MS liquid medium which is containing 0.6 mg/l TDZ, 0.3 mg/l NAA and 0.2 mg/l IBA. Different volumes of liquid medium have been used, 30 ml of medium flask showed the maximum number of shoots. Liquid medium is better suited for in vitro propagation of A. lanata since the enhanced multiplication rate was observed with shorter subculture intervals.Plant Tissue Cult. & Biotech. 31(1): 35-42, 2021 (June)